Perancangan dan Penerapan Sistem Informasi Pengarsipan Surat Berbasis Web: Solusi Tata Kelola Dokumen di Dinas Lingkungan Hidup, Kehutanan, Dan Pertanahan Provinsi Papua Tengah - Usman Arfan; Alfian Nuwa Basinung (STMIK Pesat Nabire, 2025)
Manual letter archiving in government institutions often faces various challenges, such as limited storage space, the risk of document loss, and slow information retrieval processes. This study aims to design and implement a web-based letter archiving information system as a solution to improve the efficiency and transparency of document management at the Forestry Office of Central Papua Province. The system development method adopts the Scrum approach, allowing for iterative development and adaptability to changing user needs. The system was built using the PHP programming language and a MySQL database, and includes features such as archiving incoming and outgoing letters, document tracking, quick search functionality, and archive category management. The implementation results show that the developed system significantly enhances the speed and accuracy of letter management, minimizes data entry errors, and strengthens institutional accountability and operational efficiency. This system provides a substantial contribution to the digitalization of public administration services, particularly in managing official documents.